A combined approach of methods for determining the regional assessment of the disjunct plant Primula pedemontana in Spain. (4th March 2017) - Alfaro-Saiz, E.; Alonso-Redondo, R.; Rodríguez, A.; Ruiz de Gopegui, J. A.; García, L.; García-González, M.
Abstract: The aim of this study was to conduct a regional threat-status assessment for Primula pedemontana Thomas ex Gaudin in Spain. This is an Alpine plant with a single isolated Iberian population. A major field survey was made to monitor the species in Spain with a view to preventing its possible disappearance. For that purpose, a habitat study was carried out, regional population size and population structure were determined, and major threats and conservation actions were identified. Besides, habitat suitability maps were drawn up for the present and for 2025 and the percentage of potential habitat loss was calculated in order to estimate their possible evolution. The number of mature individuals, calculated as a trapezoidal fuzzy number, was [9179; 10820; 19002; 22342]. Extent of occurrence and area of occupancy calculated were 2.5 and 0.16 km 2, respectively. The regional IUCN category obtained for P. pedemontana was "Critically Endangered". The percentage of potential habitat loss was estimated at 10.9% for 2025. The authors consider that this species is among the priority Spanish plants for conservation, and that it should be included in the "Spanish List of Wild Species under the Special Protection Scheme".